2020
DOI: 10.3390/su12208652
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Strategic Management Model for Hotel Companies: A Multi-Stakeholder Proposal to “Walk the Talk” toward SDGs

Abstract: As we reach the fifth anniversary of the Declaration of the United Nations 2030 Agenda for Sustainable Development, the tourism sector responsible for over 10% of the world’s GDP still does not have an open-source, sustainable management criteria that would enable and empower them to “walk the talk” to contribute to the Sustainable Development Goals (SDGs). The purpose of this paper is to fill the gap in the social sciences and business management literature by providing a theoretical Sustainable Strategic Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 78 publications
(89 reference statements)
1
14
0
1
Order By: Relevance
“…Pertaining to efficient energy resources, reducing waste and water consumption are associated with different green practices. Studies from various scholars [5], [15], [20] have shown that energy efficiency, water savings, and waste reduction are the potential to reduce operational costs. These agreed by many studies revealed the most popular SFM practices adopted are training the employees on sustainability practices on waste management, water, and energy conservation [5], [18], [21], [24].…”
Section: Implementation Planmentioning
confidence: 99%
“…Pertaining to efficient energy resources, reducing waste and water consumption are associated with different green practices. Studies from various scholars [5], [15], [20] have shown that energy efficiency, water savings, and waste reduction are the potential to reduce operational costs. These agreed by many studies revealed the most popular SFM practices adopted are training the employees on sustainability practices on waste management, water, and energy conservation [5], [18], [21], [24].…”
Section: Implementation Planmentioning
confidence: 99%
“…The number of workers in the tourism sector, especially hotel and restaurant employees, has been laid off. A disaster that really surprised many parties indeed, a normal and fine daily life suddenly changed (Rubio-Mozos et al, 2020). However, with the disaster experienced by Bali tourism, it can still survive.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits obtained by destinations based on community participation are: 1) Can form and improve the entrepreneurial spirit of the community, 2) motivate the community to improve their ability to develop tourist destinations in their area, 3) develop the destination according to the needs of the local community, and 4) reduce the dependence of the community with government assistance and subsidies so that the implementation of the development of these tourist destinations becomes more independent. The main goal of community-based tourism is full community involvement in the development of tourist destinations and the end, will create prosperity and preserve of local wisdom from these destinations (Rogerson & Baum, 2020;Rubio-Mozos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%